Daya Hambat Ekstrak Bunga Kenanga (Cananga odorata) dan Rosella (Hibiscus sabdariffa L.) terhadap Staphylococcus aureus ATCC BAA - 1026, Pseudomonas aeruginosa ATCC 27853 dan Proteus mirabilis ATCC 2593 - Zuraida, Zuraida; Nurdiani, Catu Umirestu; Rahayu, Cahyawati; Permana, Atna; Hariutami, Desi (Anakes : Jurnal Ilmiah Analis Kesehatan, 2025)
Nosocomial infections or healthcare-associated infections (HAIs) are global health problems caused by pathogenic microorganisms, particularly antibiotic-resistant bacteria such as Staphylococcus aureus, Pseudomonas aeruginosa, and Proteus mirabilis. The increasing incidence of antibiotic resistance highlights the need to explore alternative antibacterial agents derived from natural products. This study aimed to evaluate the antibacterial activity of kenanga (Cananga odorata) and rosella (Hibiscus sabdariffa L.) flower extracts against Staphylococcus aureus ATCC BAA-1026, Pseudomonas aeruginosa ATCC 27853, and Proteus mirabilis ATCC 2593. The antibacterial activity was assessed in vitro using the disc diffusion method with various extract concentrations. The inhibitory activity of kenanga flower extract at a concentration of 100% showed average inhibition zone diameters of 27.50 mm against Staphylococcus aureus, 26.20 mm against Pseudomonas aeruginosa, and 24.20 mm against Proteus mirabilis. Meanwhile, rosella flower extract at a concentration of 100% produced average inhibition zone diameters of 33.10 mm against Staphylococcus aureus, 28.00 mm against Pseudomonas aeruginosa, and 25.20 mm against Proteus mirabilis. The results indicate that both kenanga and rosella flower extracts exhibit antibacterial activity against all tested bacteria, with inhibitory strength varying according to extract concentration. Rosella extract demonstrated higher inhibitory activity against Staphylococcus aureus, whereas kenanga extract showed significant antibacterial activity against specific test bacteria. In conclusion, kenanga and rosella flower extracts have potential as natural antibacterial alternatives to help control bacterial infections associated with nosocomial infections.   Keywords:  Antibacterial, Cananga odorata, Hibiscus sabdariffa L., Nosocomial infection, Antibiotic                                     resistance